Psychometric networks and their implications for the treatment and diagnosis of psychopathologies - Ramos Vera, Cristian (2022)
In this chapter, we present the main methodological principles of psychological networks as a way of conceptualizing mental disorders. In the network approach, mental disorders are conceptualized as the consequence of direct interactions between symptoms, which may involve biological, psychological, and social mechanisms. If these cause-and-effect relationships are strong enough, symptoms can generate a degree of feedback to sustain them. It is discussed how such an approach contrasts with the traditional psychometric approach, known as the Latent Variable Theory, which assumes that disorders are constructs that exist but are not directly observable. Furthermore, it is also discussed how new neuropsychological hypotheses have been derived in the network approach and how such hypotheses generate direct implications for the understanding of diagnosis and treatment of psychological disorders. Finally, the recentness of the network approach in psychology and how future studies can establish its robustness are discussed.